Influence of potato variety and PVY infection on aphid behaviour: preferences from Myzus persicae and Macrosiphum euphorbiae. Issue 1 (June 2021) - Zhou, Haibo; Yu, Teng; Chen, Longsheng; Li, Weiwen; Dong, Ling; Sun, Song
Abstract: In order to determine the potential effects of potato plant infected by Potato virus Y (PVY) on the biology of aphid vectors, plastic box experiments were set up to study the preference of two of the most efficient PVY vectors, Myzus persicae (Sulzer) and Macrosiphum euphorbiae (Thomas). Aphid-plant selections were assessed 4h and 8h after aphid set in observation chamber presenting dual choices using two potato varieties, cv. Désiré e and cv. Bintje. Experiments show that both M. persicae and M. euphorbia preferentially settled on cv. Bimtie potato plants infested by PVY when compared to healthy potato plants after 4h and 8h. Compared healthy cv. Désirée plant and infested cv. Désirée plant, M. persicae tended to choose healthy plant, no significant preference for M. euphorbiae was found. When both cv. Bintje and cv. Désirée plant were infested by PVY, M. persicae tended to choose cv. Désirée plant, whereas M. euphorbiae made a choice to cv. Bintje plant. While the healthy plants were also compared, no significant preference for M. euphorbiae was observed, M. persicae preferred to cv. Désirée plant in dual-choice experiment. Results of our studies could help to further increase the knowledge on aphid dynamics and viral epidemiology in the potato cropping systems.